2010
DOI: 10.3109/07357907.2010.512603
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of E-Cadherin Expression and CDH1 Promoter Methylation in Patients With Endometrial Carcinoma

Abstract: The primary aim of this study is to evaluate the clinical significance of E-cadherin protein expression and the methylation status in CDH1 promoter in endometrial cancer. The expression of E-cadherin and methylation in its promoter region was analyzed, retrospectively, in 152 clinical tissue samples from patients with endometrial lesions. We found that the hypermethylation of CDH1 promoter, which caused low expression of E-cadherin in endometrial cancer, was associated with not only clinicopathological progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…A few studies have evaluated the promoter methylation of CDH1/E-cadherin, a possible tumor-suppressor gene, in endometrial cancer (14,(46)(47)(48)(49). In the present study, we detected CpG promoter methylation of this gene in 31.4% of EEC samples, 21.1% of EHP cases and in 20.0% of cases with healthy endometrium.…”
Section: Rassf1a Gstp1 Cdh1supporting
confidence: 56%
See 1 more Smart Citation
“…A few studies have evaluated the promoter methylation of CDH1/E-cadherin, a possible tumor-suppressor gene, in endometrial cancer (14,(46)(47)(48)(49). In the present study, we detected CpG promoter methylation of this gene in 31.4% of EEC samples, 21.1% of EHP cases and in 20.0% of cases with healthy endometrium.…”
Section: Rassf1a Gstp1 Cdh1supporting
confidence: 56%
“…A higher methylation rate of the CDH1 gene (42.9% in EEC) was detected by Kang et al (36) who also described the high frequency of this event in cervical squamous cell carcinoma (80.6%). The association between CDH1 promoter hypermethylation and endometrial cancer was also analyzed by Yi et al (49) who found that the hypermethylation of the CDH1 promoter, which caused low expression of E-cadherin in endometrial cancer, was associated with not only clinicopathological progression of endometrial cancer but also with the overall 5-year clinical survival rate. The findings provide a potential therapeutic and prognostic target molecule for patients with endometrial cancer.…”
Section: Rassf1a Gstp1 Cdh1mentioning
confidence: 95%
“…As previously shown, CDH1 expression is often reduced or completely inactivated by promoter methylation. A low E-cadherin expression is associated with worse prognosis, higher stage and greater metastatic potential (39). Our previous experiments conducted on breast and colon cancer lines confirm that an increase of WWOX expression level results in changes in cell behavior (23, unpublished data).…”
Section: Discussionmentioning
confidence: 61%
“…[17]. The loss of E-cadherin expression in EEC is associated not only with the CDH1 gene mutations [17], but also with CDH1 promoter hypermethylation [18] and dysregulation of the proteins, which normally inhibit the E-cadherin expression. The loss of E-cadherin expression is a poor prognostic factor for the patients with EEC [10], because this loss is associated with the phenomenon of epithelial-mesenchymal transformation, which includes the loss of apical-basal polarity of the cancer cells, the increasing of the mesenchymal integrins synthesis by these cells, the migration of the tumor cells into the adjacent tissues and also the tumor metastasis [19].…”
Section: Resultsmentioning
confidence: 99%